Arabic as A Language Between Qur'anic (sacred) and Historical Designation - Salleh, Kamarudin (Buletin Al-Turas, 2018)
In this short essay, basically break down the discussion into three main parts. In the introductory part. glance briefly on the origins of arabiyah and the founding of lslamic religion as a focal point in shaping and solving the Arabic language. The second part, the elaboration revolves on historical change and renewal in Arabic during the early islamic Era (Arabic Poetry)and Middle Age in a wide sense includes the development of knowledge and attitude of scholars at that time. And the last section. wholly discovering the Modern problems of changing and renewal in Arabic. I choose two contemporary scholars in Middle East commenting on this issue.